ANALISIS PERBANDINGAN BIAYA DAN PENDAPATAN PENGGUNA PUPUK ORGANIK DAN ANORGANIK PADA USAHA TANI PADI SAWAH IRIGASI DI DESA RAMBAH TENGAH HILIR KECAMATAN RAMBAH KABUPETEN ROKAN HULU - -, Fauzi (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2016)
This study aims to determine the costs and farm income as well as the level of efficiency of inorganic and organic rice farming on irrigated fields in the village of Central Rambah Rambah Rokan Hilir District of Hulu. Determination of sampling in this study using purposive sampling technique in which respondents selected 20 farmers are organic rice and 20 rice farmers in the village of inorganic Middle Rambah Rambah Rokan Hilir District of Hulu. Data collection techniques used were observation and interviews. Data were analyzed by using quantitative descriptive analysis techniques. The results showed that the total cost per hectare and per kg of output per growing season issued an organic rice farm larger than inorganic rice farming, the value of organic rice farming RC ratio greater than inorganic rice farming. This suggests that organic rice farming is more profitable than rice farming inorganic. Suggestions put forward is organic rice farming are equally worth the effort, but the rice farming fertilizer users Organic rice farming more profitable than inorganic fertilizer users.